Análise química e avaliação das atividades biológicas da geoprópolis de abelha jandaíra (melipona subnitida) nativa do Semi-Árido Nordestino - Sousa, Déborah Munique Nogueira de (Universidade Federal Rural do Semi-Árido, 2013)
Propolis is a resinous material of varying color and consistency, obtained by bees through collect of resin flora of the region, and altered by the action of enzymes contained in their saliva. The native bees from the tribe Meliponini add clay and/or land to their propolis, originating geopropolis. In this study, samples of jandaira’s geopropolis (Melipona subnitida), obtained from a semi-arid region, were characterized morphologically and chemically, by light microscopy and Thin Layer Chromatography (TLC) and Liquid Chromatography with UV/Diode Array Detection (LC-UV/DAD) respectively; parallel to this was quantified total phenols content. In addition, biological activities were investigated in vitro and in vivo, such as antioxidant activity (by DPPH), antibacterial activity (by agar diffusion method), healing activity, through the induction of experimental surgical wounds in rats and finally, a preliminary toxicity test on Artemia salina with a sample was performad. The samples exhibited organoleptic characteristics similar to each other and were rich in pollen grains predominantly belonging to the subfamily Mimosoideae. By TLC and LCUV/ DAD, two chemical profiles was demonstrated, one predominantly composed of flavonols and flavones and the other rich in tannins and phenolic acids, such as gallic acid. The total phenolic content varied between 2.845 ± 0.059 % and 11.291 ± 0.262%. Highest antioxidant capacity was conferred by the sample A6 (IC50 = 0.084 %). The extract without wax, obtained from this sample (ESC6) showed bad inhibitory effects against four strains of bacteria. In the assay healing, cream Melipona subnitida’s geopropolis 10 % decreased signs of inflammation, stimulated angiogenesis and collagen production, advancing the process of re-epithelialization in the treated animals, however only on the 14th post-operative day was seen difference statistically significant between the areas of wounds of experimental and control groups. The sample tested on Artemia salina averaged LC50 of 1282.61 mg / mL, demonstrating low toxicity. Finally, we can conclude that the jandaira’s geopropolis, obtained in the semi-arid region, is an important source of phenolic compounds, may be used in nonconventional medicine as an antioxidant and wound healing agent
Keywords: Geoprópolis; Melipona subnitida; Perfil químico; Atividades biológicas; Geopropolis; Melipona subnitida; Biological activities; CIENCIAS AGRARIAS::MEDICINA VETERINARIA